AKIBAT HUKUM PERKAWINAN KEPADA ANAK YANG TIDAK DICATATKAN - Yugos Novia Hulu (Jurnal Panah Hukum, 2023)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on Belief in One Almighty God. Marriage must be registered in the civil registry based on Law Number 1 of 1974 concerning Marriage. Based on Article 2 paragraph (1) and (2) of Law Number 1 of 1974 concerning Marriage. Paragraph (1) stipulates that marriage is valid if it is carried out according to the laws of each religion and belief. Paragraph (2) determines that each marriage is recorded according to the applicable laws and regulations. From this article it can be understood that marriages that are not registered in the civil registry are declared invalid in the eyes of the law even though the marriage has been registered according to their respective religions and beliefs. The type of research used in this study is sociological legal research using the applicable laws and regulations approach. Data collection was carried out by interviews and accurate document studies. The data analysis used was descriptive qualitative analysis and conclusions were drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the Department of Population and Civil Registration has tried to socialize the importance of registering marriages at the sub-district level and several churches in South Nias Regency. The author suggests that the Head of Dukcapil and the party responsible for Civil Registration should socialize the importance of Marriage Registration not only at the sub-district level or several churches but socialize it thoroughly in every village in South Nias Regency, so that all the people of South Nias Regency understand with all of the importance of registration of marriages